Epidemiology and classification of lumbosacral spondylolisthesis - Wójcik, Gustaw (Journal of Education, Health and Sport, 2017)
Spondylolisthesis is a disease of the locomotive organs associated with instability of the vertebral column. The mechanism of this pathology is based on the dislocation (subluxation) of the vertebrae along with the whole spine higher up front to the lower body vertebral. This condition usually causes complete loss of spine stability, decreased patient performance, appearance of pain, and possible presentation of various neurological symptoms. The most common localization of the spondylolisthesis is lumbosacral joint. The characteristic feature of the spondylolisthesis is that it is unique to the human race. There are many classification of spondylolisthesis, taking into account different variables, including the etiology of their formation, location, degree of slippage or aggravation of ailments. Each of these classifications gives you the opportunity to assess the severity of the disease, allowing you to plan for effective treatment.